Outdoor Fitness Zone: utilization pattern, and environmental and individual characteristics associated with the volume of utilization - Debora Bernardo da Silva; Emerson Sebastião; Thiago Ferreira de Sousa; Sheilla Tribess; Camila Bosquiero Papini (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: To examine the association between environmental and individual characteristics and utilization pattern of Outdoor Fitness Zones (OFZ) with the volume of utilization of these public spaces in Uberaba, Brazil. Methods: Cross-sectional descriptive study. Data collection was conducted using "in loco" interviews (three different days and times) and direct observation of nine OFZ. Poisson regression analysis was used to estimate prevalence ratios using the volume of utilization higher than 90 min per week as the dependent variable and a collection of socio-demographic, environmental, utilization pattern, and OFZ characteristics as independent variables. Results: Adjusted analysis revealed that volume of utilization higher than 90 min per week of OFZ was associated with a higher prevalence ratio among users utilizing such spaces to meet friends sometimes (PR = 2.43; 1.21-4.90) and always (PR = 3.43; 1.61-7.34) compared to not meeting friends. A lower prevalence ratio was found in users who attend the OFZ only during the week or only weekend days (PR = 0.52; 0.37-0.73) compared to a user who attends both (week and weekends days). OFZ not providing a space for walking or jogging (PR = 0.48; 0.23-0.99) were also associated with a lower prevalence ratio of utilization higher than 90 min per week. Conclusions: The findings demonstrated that most individual and environmental characteristics and utilization patterns of the OFZ in the city of Uberaba, MG, Brazil, were not associated with the volume of utilization. Users who meet friends and attend both week and weekend days OFZ that features walking or running trails were associated with a higher volume of utilization.